A hybrid approach for selection of most sustainable cooking fuel in the Indian context. (2017) - Sindhwani, Rahul; Mittal, Varinder Kumar; Singh, Punj Lata; Kalsariya, Vivek; Tewari, Anurag
The literature on cooking fuel strongly supports that indoor air pollution and environmental emissions affect the user health and global environment sharply. This paper identifies seven cooking fuels viz. wood, coal, kerosene, biogas, liquefied petroleum gas (LPG), piped natural gas (PNG), and electrical induction in an Indian context. The analysis of the alternative fuels on the basis of six criteria would provide opportunities to the users for shifting to most sustainable cooking fuel (MSCF). In this paper, an attempt has been made to assess the MSCF using entropy approach, MOORA method, and VIKOR analysis. This study concludes that electrical induction is MSCF followed by PNG and LPG respectively. The study provides the scientific evidence for the MSCF alternative in Indian context which will directly benefit the society.